Correlates of Cognitive Function in Sickle Cell Disease: A Meta-Analysis. (22nd January 2020) - Prussien, Kemar V; Siciliano, Rachel E; Ciriegio, Abagail E; Anderson, Allegra S; Sathanayagam, Radha; DeBaun, Michael R; Jordan, Lori C; Compas, Bruce E
Abstract: Objective: To provide a comprehensive quantitative review of biological, environmental, and behavioral correlates across domains of cognitive function in sickle cell disease (SCD). Methods: Forty-seven studies were identified in PubMed, MedLine, and PsycINFO involving 2573 participants with SCD. Results: Meta-analytic findings across all identified samples indicate that hemoglobin and hematocrit were positively correlated with Full Scale IQ [FSIQ; r = .15, 95% confidence interval (CI) = .10 to .21], language and verbal reasoning ( r = .18, 95% CI = .11 to .24), and executive function ( r = .10, 95% CI = .01 to .19) with small effects and significant heterogeneity. Transcranial Doppler velocity was negatively associated with visual spatial and perceptual reasoning ( r = −.18, 95% CI = −.31 to −.05). Socioeconomic status was positively associated with FSIQ ( r = .23, 95% CI = .17 to .28), language and verbal reasoning ( r = .28, 95% CI = .09 to .45), visual spatial and perceptual reasoning ( r = .26, 95% CI = .09 to .41), and executive function ( r = .18, 95% CI = .07 to .28) with small to medium effects. Finally, total behavioral problems were negatively associated with FSIQ ( r = −.12, 95% CI = −.21 to −.02) such that participants with lower FSIQ exhibited greater behavioral and emotional problems. Conclusions: Findings provide evidence for biological, environmental, and psychosocial corelates across multiple domains of cognitive function in SCD. More research on more specific cognitive domains and psychosocial correlates is needed in addition to assessments of interactional models among risk factors.